Kinetic and equilibrium studies of fluoride adsorption by a carbonaceous material from pyrolysis of waste sludge - Volkan Dogan; Serdar Aydın (Химия и технология воды, 2016)
The efficiency of the adsorption for fluoride by sludge from the treatment of starch industry wastewater was investigated. Batch experiments were conducted in order to determine the parameters that affect the adsorption process. The activation for waste sludge and specific surface area and porosity effects in enhancing the pyrolysis conditions were determined. The adsorption parameters of initial fluoride concentration, pH and adsorbent dosage were investigated with carbonaceous material. As a result of pyrolysis of samples treated with ZnCl₂ 11% m²/g; the specific surface area was reached. Correlation coefficient of 0.99 and 12.75 mg/g adsorption capacity and adsorption isotherm model were revealed as convenient. Experimental results show that the adsorption of fluoride waste sludge will be effective in many ways in which the adsorbent is applied.